Changes in Symptoms Experienced by SARS-CoV-2-Infected Individuals – From the First Wave to the Omicron Variant - Schulze, Hansjörg; Bayer, Wibke (Frontiers in Virology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic and public health crisis since the beginning of 2020. First recognized for the induction of severe disease, the virus also causes asymptomatic infections or infections with mild symptoms that can resemble common colds. To provide better understanding of these mild SARS-CoV-2 infections and to monitor the development of symptoms over time, we performed a detailed analysis of self-reported symptoms of SARS-CoV-2 positive and SARS-CoV-2 negative individuals. In an online-based survey, a total of 2117 individuals provided information on symptoms associated with an acute respiratory infection, 1925 of the participants had tested positive for SARS-CoV-2 infection, and 192 had tested negative. The symptoms reported most frequently during the early phases of the pandemic by SARS-CoV-2 infected individuals were tiredness, headache, impairment of smell or taste and dry cough. With the spread of the alpha and delta variants, the frequency of nose symptoms such as blocked or runny nose and sneezing increased to being reported by almost 60% of infected individuals. Interestingly, the spread of the omicron variant brought a sharp decrease in the incidence of impaired sense of smell or taste, which was reported by only 24% in this phase of the pandemic. The constellation of symptoms should be monitored closely in the months ahead, since future SARS-CoV-2 variants are likely to bring about more changes.